The banking systems of Germany, the UK and Spain form a spatial perspective: The German case - Franz Flögel; Stefan Gärtner (Institut Arbeit und Technik (IAT), 2018)
A comparison of the German banking system with that of the United Kingdom (UK) and Spain shows Germany to be decentralised not only regarding the distribution of banks, but also its financial and political system more generally. Decentralised banks, which are predominantly regional savings banks and cooperative banks in Germany, nearly account for most lending to business and have extended lending at the expense of centralised banks (such as the four big banks, for example). Federalism and strong redistribution mechanisms between the regions support decentralised banking in Germany. Furthermore, close cooperation in their banking groups is shown to allow decentralised banks to realise economies of scale and develop superior techniques for retail banking, like bank-ICT and rating systems. The detailed comparison of a savings bank with a big bank suggests that shorter (functional) distances allow regional banks to consider soft information easily and reliably when lending to SMEs. Short-distance lending not only reduces the financial constraints of (financially distressed) SMEs, but can also be profitable for banks as they are able to realise higher interest earnings in business with informationally opaque enterprises. However, decentralised banking is also under threat in Germany due to tightening (more complex) banking regulations and the continuing low interest rate environment. Therefore, decentralised banks need to cut costs, which is why they have merged to larger units and closed branches in recent years. Furthermore, they have tried to increase fee earnings at the risk of disintermediation. This paper identifies two dilemmas of these cost-cutting strategies. First, disintermediation challenges regional savings-investment cycles and thus regional independency. Second, mergers, branch closures and the standardisation of processes endanger local decision-making authority and hence short-distance lending. As the detailed comparison make clear, the ability of regional banks to decide on credit at a short distance enables profitable lending to informationally opaque SMEs, meaning SMEs that appear to be very risky on the basis of hard information, by utilising soft information. Accordingly, short distance tends to be a key competitive advantage of regional banks, especially in a low interest rate environment. Cost-cutting measures must be conducted with full awareness of this advantage. With respect to lending to SMEs, branch closures may be less critical than mergers and standardisation because most branches are not involved in lending to SMEs anyway.
Keywords: D43; E21; G01; G21; G38; R12; 330; comparing banking systems; SME finance in Germany; savings and cooperative banks; decentralised vs. centralised banking